A technical review on characterization methods for structures and properties of emulsion - Xuncheng Shi; Dawei Qi; Caihong Lin; Jianwei Li (APL Materials)
Emulsions, particularly in the pharmaceutical, cosmetic, and food industries, are essential for the delivery and stabilization of active ingredients. Due to their structural complexity—including variations in droplet size, phase distribution, and interfacial properties—characterizing emulsions is essential for optimizing their performance and stability. Existing reviews tend to focus on specific emulsion types, properties, or individual characterization techniques, often failing to provide a holistic assessment. Consequently, there is a critical need for a comprehensive review that integrates various characterization methods. This review addresses this gap by systematically evaluating key techniques, including scattering methods (dynamic light scattering, small-angle x-ray scattering), spectroscopic techniques (Fourier transform infrared and nuclear magnetic resonance spectroscopy), microscopy methods (scanning electron microscopy, confocal laser scanning microscopy), and rheometry. By consolidating the strengths and limitations of each method, this review offers a unified framework to guide researchers in selecting appropriate techniques for characterizing emulsions, ultimately contributing to the optimization of their structure, properties, and performance across diverse applications.